2018
DOI: 10.1021/acs.chemmater.8b01173
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of Polyphenol-Poloxamer Nanovesicles for Targeting Inflammatory Bowel Disease Therapy

Abstract: Currently, there is no curative treatment for inflammatory bowel disease (IBD), which has an increased risk of colitis-associated cancer. Corticosteroids are the main clinical IBD therapeutics but have significant side effects. Even heavy corticosteroid use can result in the failure of IBD treatment which may lead to resective surgery. In this study, we designed one type of new drug-delivery system (DDS) delivering dexamethasone (DEX), an anti-inflammation corticosteroid, for IBD therapy. This DDS was screened… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
81
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(81 citation statements)
references
References 52 publications
(65 reference statements)
0
81
0
Order By: Relevance
“…Stability Investigation of CeO 2 @MMT (1:9) in Simulated Gastric Juice: The stability of CeO 2 @MMT(1:9) was evaluated as follows. First, to simulate the digestion process of food in the stomach, 200 mg of CeO 2 , MMT, or CeO 2 @MMT(1:9) were added into 10 mL of hydrochloric acid solution (as a gastric fluid simulating fluid, pH at 1.2 to 1.5) and incubated at 37 °C with 65 rpm shaking for 4 h. [25] Then, CeO 2 , MMT, or CeO 2 @MMT(1:9) were neutralized by washing with water and NaOH solution (0.1 mm). Finally, the materials were dissolved in water or lyophilized for TEM, XRD, ICP, zeta potential measurements, and analysis of ROS scavenging activities.…”
Section: Sod-like Activity Measurementsmentioning
confidence: 99%
“…Stability Investigation of CeO 2 @MMT (1:9) in Simulated Gastric Juice: The stability of CeO 2 @MMT(1:9) was evaluated as follows. First, to simulate the digestion process of food in the stomach, 200 mg of CeO 2 , MMT, or CeO 2 @MMT(1:9) were added into 10 mL of hydrochloric acid solution (as a gastric fluid simulating fluid, pH at 1.2 to 1.5) and incubated at 37 °C with 65 rpm shaking for 4 h. [25] Then, CeO 2 , MMT, or CeO 2 @MMT(1:9) were neutralized by washing with water and NaOH solution (0.1 mm). Finally, the materials were dissolved in water or lyophilized for TEM, XRD, ICP, zeta potential measurements, and analysis of ROS scavenging activities.…”
Section: Sod-like Activity Measurementsmentioning
confidence: 99%
“…Owing to the unavailability of appropriate therapeutics for treatment of IBD, corticosteroids till date poses as the main clinical IBD therapeutics in spite of having significant side effects. Heavy corticosteroid use may even result in the failure of IBD treatment leading to respective surgery (Wang et al, 2018). Such drugs are administered orally.…”
Section: Colonic Drug Delivery and Its Physiological Landscapementioning
confidence: 99%
“…At neutral pH both S1 and S2 remained capped, however on exposure to a reducing environment such as in the presence of sodium dithionite, payload release enhanced significantly. IBD therapy proposed by Wang et al (2018) involved a newly designed drug-delivery system that delivered an anti-inflammatory corticosteroid called dexamethasone (Dex). Study results revealed that in presence of esterase, 10% Dex loaded, PPNP-Dex (polymers self-assembled nanoparticledexamethasone) exhibited responsive release behavior.…”
Section: Colonic Drug Delivery and Its Physiological Landscapementioning
confidence: 99%
“…The increased permeability of epithelium allows the nanoparticles to accumulate in the inflamed intestine through oral delivery 28 , 29 . In previous work, we developed polyphenol-poloxamer self-assembled supramolecular nanoparticles for oral delivery in IBD therapy 30 . Natural polyphenols such as tannic acid (TA) and epigallocatechin gallate (EGCG) are rich in galloyl and catechol groups that form hydrogen bonds and hydrophobic interactions with various proteins and peptides 31 , 32 .…”
Section: Introductionmentioning
confidence: 99%